Piezotronic Sensor for Bimodal Monitoring of Achilles Tendon Behavior - Zihan Wang; Shenglong Wang; Boling Lan; Yue Sun; Longchao Huang; Yong Ao; Xuelan Li; Long Jin; Weiqing Yang; Weili Deng (Nano-Micro Letters)
Highlights The underlying mechanism governing the modulation of carrier transport by piezoelectric potential is elucidated through finite element simulations and experimental validation. The bimodal piezotronic sensor (BPS) exhibits exceptional responsiveness to both static and dynamic stimuli, achieving an ultrahigh gauge factor of up to 23,439. The BPS demonstrates robust capability for bimodal monitoring and hazard warning of Achilles tendon behavior, achieving an accuracy of 96%.